2015
DOI: 10.1007/s10709-014-9807-0
|View full text |Cite
|
Sign up to set email alerts
|

An improved taxonomic sampling is a necessary but not sufficient condition for resolving inter-families relationships in Caridean decapods

Abstract: During the past decade, a large number of multi-gene analyses aimed at resolving the phylogenetic relationships within Decapoda. However relationships among families, and even among sub-families, remain poorly defined. Most analyses used an incomplete and opportunistic sampling of species, but also an incomplete and opportunistic gene selection among those available for Decapoda. Here we test in the Caridea if improving the taxonomic coverage following the hierarchical scheme of the classification, as it is cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 36 publications
3
31
1
2
Order By: Relevance
“…The non-monophyly of Pasiphaeidae has been suspected hitherto 31 , with a recent recalibration of the constituent genera 32 . Despite considerable progress towards resolving the problematic phylogeny of Hippolytidae sensu lato 30 , further studies found additional polyphyly 33 , consistent in generic scope with the present analysis. The division of the older concept of Oplophoridae into two families 34 has remained controversial 35 , with one genus— Systellaspis —occupying an intermediate position between two families, as in the present analysis.
Fig.
…”
Section: Resultssupporting
confidence: 84%
“…The non-monophyly of Pasiphaeidae has been suspected hitherto 31 , with a recent recalibration of the constituent genera 32 . Despite considerable progress towards resolving the problematic phylogeny of Hippolytidae sensu lato 30 , further studies found additional polyphyly 33 , consistent in generic scope with the present analysis. The division of the older concept of Oplophoridae into two families 34 has remained controversial 35 , with one genus— Systellaspis —occupying an intermediate position between two families, as in the present analysis.
Fig.
…”
Section: Resultssupporting
confidence: 84%
“…Shrimp exhibit a stunning variety of claw forms (Figures 1; Figures S1-S4). When claw-joint types for first and second pereopods (hereafter P1 and P2) were mapped onto published phylogenies [13,16,17], we reconstructed five phases to snapping-claw evolution: (1) pivot joint / (2) slip joint / (3) cocking (torquereversal) slip joint / (4) cocking slip joint with cavitation (snap) / (5) cocking pivot joint with cavitation ( Figure 2) (see Table S1 for claw-joint states and closing modes for all taxa; STAR Methods for claw imaging, scoring, and character mapping protocols; Figures SM3-SM9 in Methods S1 for implications of alternate phylogenies; and Ultrafast Closing in Caridean Shrimp Claws: A Novel Cocking Mechanism for biomechanical details). Throughout our discussion, by ''snap'' we mean ''snap with cavitation,'' and we refer to the major claw for taxa with asymmetrical P1 or P2 chelae.…”
Section: Comparative Morphology and Evolutionary History Of Shrimp CLmentioning
confidence: 99%
“…Locations are coded as follows: RI for Reunion Island, NC for New Caledonia, FP for French Polynesia and LNI for northern Line Islands. [1] 74 ; [2] 75 ; [3] 76 ; [4] 77 ; [5] 9 ; [6] 78; DS direct submission.…”
Section: Figurementioning
confidence: 99%